2009
DOI: 10.1002/adma.200800582
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibers Extruded Artificially from Aqueous Solutions of Regenerated Bombyx mori Silk Fibroin are Tougher than their Natural Counterparts

Abstract: The dragline silk of certain spiders has excellent tensile properties [1] that are maintained over a remarkable temperature range.[2] Although the commercial Mulberry Silkworm (Bombyx mori) silk is considerably weaker and less tough than the best spider dragline silks, fibers with comprehensive mechanical properties approaching that of spiders can be obtained by force-reeling directly from silkworms.[3] Remarkably, both spider and silkworm silks are spun naturally from aqueous protein solutions at very low hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
189
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(202 citation statements)
references
References 30 publications
(20 reference statements)
10
189
1
Order By: Relevance
“…The estimated values (see above) of ultimate true stress (o-u ; MPa) and Young modulus (ÂŁ; GPa) obtained after ethanol immersion of both as-spun threads (SI and S2), but especially those of S2 (266 MPa and 30 GPa for Sl-E and 404 MPa and 32 GPa for S2-E), compare well not only with the values reported in the literature for regenerated silk fibroin fibers [53,[76][77][78], but also with those of natural B. mori silk [47].…”
Section: Mechanical Properties Of Aligned Threadssupporting
confidence: 71%
See 1 more Smart Citation
“…The estimated values (see above) of ultimate true stress (o-u ; MPa) and Young modulus (ÂŁ; GPa) obtained after ethanol immersion of both as-spun threads (SI and S2), but especially those of S2 (266 MPa and 30 GPa for Sl-E and 404 MPa and 32 GPa for S2-E), compare well not only with the values reported in the literature for regenerated silk fibroin fibers [53,[76][77][78], but also with those of natural B. mori silk [47].…”
Section: Mechanical Properties Of Aligned Threadssupporting
confidence: 71%
“…Ultimate stress (a u ) values for as-spun threads (SI and S2) range from 196 to 360 MPa, depending on the particular batch tested ( Table 2). These values are comparable with the best bio-inspired fibers [53,[76][77][78] and remarkably close to those found in degummed natural silk fibers (300-600 MPa) [47], Similar outstanding results were obtained here for the Young moduli (ÂŁ, GPa) of as-spun fibers (14-20 GPa; Table 2), which resemble those of natural silk fibroin (9-17 GPa) [47] However, it should be noted that the actual densities of the threads made from aligned fibers in our study can be significantly lower than that of natural silk, due to the lower crystallinity of the electrospun fibers and the voids between them. Therefore, both the ultimate stress (a u ) and the initial elastic moduli (ÂŁ, GPa) -calculated from the assumption made aboveshould be taken with caution.…”
Section: Mechanical Properties Of Aligned Threadssupporting
confidence: 70%
“…[17][18][19] However, it still has problematic characteristics for further clinical applications and use in industrial processes, such as low stiffness and high production cost. 20,21 For this reason, several attempts have been made to improve the properties of silk biomaterials, and this field has become a rapidly growing area of biomaterial research. [22][23][24] Research has demonstrated that the main inorganic component of human bone tissues, HAP, enhances the compressive strength of silk biomaterials and also induces new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…This drawing process orients the silk proteins along the longitudinal axis of the fibers and improves the fibers' mechanical properties. The post-spin drawing process used by silkworms and spiders has been replicated in conventional processes to improve the mechanical properties of the artificial showed mechanical properties comparable to those of the natural silkworm silk fibers ( Figure 3C) (Zhou et al, 2009;Yan et al, 2010). The same spinning process was applied by Chen's group to a spinning dope composed of a silk fibroin-CNT composite to prepare strong artificial fibers with breaking energies comparable to that of the spider dragline silk fibers (Fang et al, 2015).…”
Section: Post-spin Drawing Processmentioning
confidence: 99%